2013
DOI: 10.3748/wjg.v19.i14.2262
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus induces expression of cholesterol metabolism-related genesviaTLR2 in HepG2 cells

Abstract: Ad-HBV increases LDLR and HMGCoAr expression, resulting in exacerbated cholesterol accumulation in HepG2 cells, which was mediated via the TLR2 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 29 publications
1
28
0
1
Order By: Relevance
“…We considered this cellular cholesterol overload as the key driver of ACAT stimulation [44] leading to the esterification of free cholesterol excess into intracellular cholesterol pools (lipid droplet accumulation) and decreased the amount of plasma membrane free cholesterol, diminishing the free cholesterol gradient requested for passive diffusion, a key macrophage cholesterol efflux regulator in normolipidemic conditions [36]. Our observations are in line with previous observations demonstrating that TLR4 and TLR2 agonists can upregulate SREBP2, HMGCR, and LDL-R expression and promote foam cell formation independently of oxidized-LDL uptake [29,45,46].…”
Section: Discussionsupporting
confidence: 89%
“…We considered this cellular cholesterol overload as the key driver of ACAT stimulation [44] leading to the esterification of free cholesterol excess into intracellular cholesterol pools (lipid droplet accumulation) and decreased the amount of plasma membrane free cholesterol, diminishing the free cholesterol gradient requested for passive diffusion, a key macrophage cholesterol efflux regulator in normolipidemic conditions [36]. Our observations are in line with previous observations demonstrating that TLR4 and TLR2 agonists can upregulate SREBP2, HMGCR, and LDL-R expression and promote foam cell formation independently of oxidized-LDL uptake [29,45,46].…”
Section: Discussionsupporting
confidence: 89%
“…These modifi cations cause triglycerides to accumulate in the hepatocyte 30 . A recent experimental study revealed that adenovirus containing the HBV genome (Ad-HBV) up-regulated the expression of genes related to cholesterol metabolism in HepG2 cells 31 , suggesting that HBV itself infl uences cholesterol metabolism. Nevertheless, the lipid profi les among individuals with chronic HBV remain a matter of debate in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HBV infection may alter hepatic cholesterol metabolism. HBV‐transfected HepG2 cells exhibited increased expression of low‐density lipoprotein receptor and 3‐hydroxy‐3‐methylglutharyl‐coenzyme A reductase (HMGCR) . In addition, a study in HBV‐infected humanized mice also revealed enhanced gene expression related to hepatic cholesterol production and uptake, including those encoding SREBP‐2, HMGCR and LDL receptor .…”
Section: Possible Mechanistic Role Of Hbv Infection In Nafld Pathogenmentioning
confidence: 99%
“…of low-density lipoprotein receptor and 3-hydroxy-3-methylglutharyl-coenzyme A reductase (HMGCR). 94 In addition, a study in HBV-infected humanized mice also revealed enhanced gene expression related to hepatic cholesterol production and uptake, including those encoding SREBP-2, HMGCR and LDL receptor. 95 Further investigation identified the pre-S1 domain of the HBV envelope as the primary contributor to this phenomenon.…”
Section: Olism Hbv-transfected Hepg2 Cells Exhibited Increased Exprementioning
confidence: 99%